Synthesis, characterization and microbial screening of some new methyl 4, 6-o-(4-methoxybenzylidene)-?-D-glucopyranoside Derivatives - Kawsar, Sarkar MA; Kabir, Abul K MS; Bhuiyan, Mohammad M R; Ferdous, Jannatul; Rahman, Mohammad S (Journal of Bangladesh Academy of Sciences, 2014)
Regioselective pentanoylation of methyl 4,6-O-(4-methoxybenzylidene)-?-D-glucopyranoside by the direct acylation method provided the methyl 4,6-O-(4-methoxybenzylidene)-2-O-pentanoyl- ?-D-glucopyranoside in good yield. A number of 3-O-acyl derivatives of this 2-O-pentanoylation product were also prepared in order to obtain new compounds and also gather additional information for structure elucidation. The chemical structure of the newly synthesized compounds was characterized by analytical and spectral methods. Synthesized acylated derivatives of Dglucopyranoside were screened for in vitro antimicrobial activities against ten human pathogenic bacteria and four plant pathogenic fungi. The study revealed that the acylated products exhibited moderate to good antimicrobial activities. It was interesting to observe that the selected compounds were more sensitive against fungal phytopathogens than those of the bacterial strains. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17554 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 145-158, 2013